Pemanfaatan Media Pembelajaran Game Edukasi Untuk Siswa SMP Berbasis Construct - Syamsul Bahri; Dwi Marisa Midyanti; Uray Ristian; Kartika Sari (LPPM POLITEKNIK LP3I, 2024)
Educational game learning media has an important role in increasing the effectiveness and efficiency of the learning process, especially for children. Currently, learning methods for children are quite effective, but some children are starting to feel bored with methods that only rely on reading and memorizing. To overcome this feeling of boredom, learning media in the form of educational games can be a good solution, considering that information and communication technology have developed rapidly and children are used to using gadgets and computers in everyday life. This construct-based educational game application can make the learning process more effective because it displays visualizations of the lessons being taught so that learning becomes more fun and has an attractive appearance. In the context of education in Indonesia, the use of educational game learning media also receives support from the government through the implementation of the 2013 Curriculum. This curriculum emphasizes competency-based learning and integrating technology in the learning process. Thus, Construct-based educational games can be an effective means to support the implementation of the 2013 Curriculum as a whole. Educational game learning media has a strong background in increasing the effectiveness and efficiency of the learning process, as well as making it more interesting and fun for children.